Law Amending and Supplementing a Number of Articles of the Law on Military Service - The National Assembly (2005)
This Law amends and supplements a number of articles of the Law on Military Service, which was passed on December 30, 1981, by the National Assembly of the Socialist Republic of Vietnam, and amended and supplemented first on December 21, 1990, and then on June 22, 1994